Does job stress mediate the risk of work disability due to common mental disorders among social workers compared with other health and social care, education, and non-human service professionals? A prospective cohort study of public sector employees in Finland - Rantonen, Otso (Nordic Association of Occupational Safety and Health NOROSH, 2025)
Objective: This study aimed to investigate (i) the risk of work disability (>10-day sickness absence spell or disability pension) due to common mental disorders (CMD) among social workers compared with other health and social care, education, and non-human service professionals and (ii) whether the risk was mediated by job stress.
Methods: A cohort of 16 306 public sector professionals in Finland was followed using survey data from baseline (2004 or if not available, 2008) on job stress [job strain or effort-reward imbalance (ERI)] and register data on work disability due to CMD from baseline through 2011. A Cox proportional hazards model was used to analyze the risk of work disability due to CMD between three occupation-pairs in a counterfactual setting, controlling for age, sex, job contract, body mass index, alcohol risk use, smoking, and physical inactivity.
Results: Social workers' job stress was at higher level only when compared to education professionals. Thus, the mediation hypothesis was analyzed comparing social workers to education professionals. Social workers had a higher risk of work disability due to CMD compared with education professionals [hazard ratio (HR) 2.08, 95% confidence interval (CI) 1.58-2.74]. This HR was partly mediated by job strain (24%) and ERI (12%). Social workers had a higher risk of work disability than non-human service professionals (HR 1.54, 95% CI 1.13-2.09), but not compared with other health and social care professionals.
Conclusions: Job stress partly mediated the excess risk of work disability among social workers only in comparison with education professionals.